Toward Financial Capability—Empowering the Young. Issue 2 (14th April 2018) - Luukkanen, Laura; Uusitalo, Outi
Abstract : The importance of enhancing financial capability is widely recognized. However, the learning outcomes from educational programs directed at young people are mixed, indicating that we may not yet have discovered the best practices. Previous studies have established that merely providing information is not the most effective way to help consumers. This study examines empowerment thinking through the dimensions of financial empowerment as a top‐down and bottom‐up approach. The article highlights two routes toward empowerment, context change, and cognition change, and their roles and potential in improving financial capability among the young. This study suggests a novel framework for promoting financial capability that is based on the dimensions of empowerment and offers tools for increasing financial capability. The study employs data from focus groups and interviews to illustrate the possible strengths and problems of empowering young people in the Finnish context.